Take my hand - Perkins-Valdez, Dolen (New York : Berkley, 2022)
In 1973 Montgomery, Alabama, Civil Townsend, a young Black nurse working for the Montgomery Family Planning Clinic, grapples with her role when she takes two young girls into her heart and the unthinkable happens, and nothing will ever be the same for any of them.
Keywords: Reproductive rights -- Fiction; Reproductive rights -- United States -- History -- 20th century -- Fiction; African American women -- Alabama -- Fiction; Involuntary sterilization -- Fiction; Eugenics -- Fiction; United States -- Race relations -- 20th century -- Fiction; Legal fiction (Literature); Historical fiction